Development of Fullerene Modified Metal Oxide Thick Films for Moisture Sensing Application. (2018) - Saha, Debdulal; Das, Sagnik
Abstract: Trace moisture sensing capability of fullerene (C60 ) modified nanoporous γ-alumina (Al2 O3 ) thick films has been presented here. Fullerene was added to create nano pore in aluminum secondary butoxide for preparation of gel tape cast thick films. One of the major advantages of using fullerene is to develop oriented nano pores (2-12 nm) throughout the ceramic thick films. The green thick films were crack free which was cast by gel tape casting process. The porosity and surface area were studied using field effect scanning electron microscope, atomic force microscope and Brunauer–Emmett–Teller. Gamma phase of alumina was also examined by X-ray diffraction analysis. The green thick films were sintered at 900 °C to obtain nanopore distribution through the surface of the thick films. Electrical characterization such as sensitivity, response, recovery and hysteresis were performed. There is no literature report on the detection of trace moisture sensor by fullerene assisted alumina sol gel tape cast process. This article explains the development of moisture sensor which can detect low range moisture (1-25 ppm) in different industrial application like gas industry, dielectric oil and drying of different food processing industry etc.